2021
DOI: 10.1140/epjds/s13688-021-00284-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of home detection algorithms on mobile phone data using individual-level ground truth

Abstract: Inferring mobile phone users’ home location, i.e., assigning a location in space to a user based on data generated by the mobile phone network, is a central task in leveraging mobile phone data to study social and urban phenomena. Despite its widespread use, home detection relies on assumptions that are difficult to check without ground truth, i.e., where the individual who owns the device resides. In this paper, we present a dataset that comprises the mobile phone activity of sixty-five participants for whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…In order to find the relationship between these most important locations, first their positions of these locations have to be determined. There are a few approaches used to find home locations via mobile phone data analysis [2,60,54,34,41].…”
Section: Home and Work Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find the relationship between these most important locations, first their positions of these locations have to be determined. There are a few approaches used to find home locations via mobile phone data analysis [2,60,54,34,41].…”
Section: Home and Work Locationsmentioning
confidence: 99%
“…Identifying the home and work locations of a subscriber is a common [19][20][21][22][23][24][25][26][27] and crucial part of the CDR processing, as these locations fundamentally determine the people's mobility customs. Furthermore, a good portion of the people live their lives in an area that is determined by only their home and workplace [19,21] or their communities [28].…”
Section: Introductionmentioning
confidence: 99%
“…After the right subscribers have been selected, it is common practice to determine users' home and work locations [8][9][10]; then, between these two crucial locations, the commuting trends can be identified. Commuting is studied between cities [9,[11][12][13] or within a city [7,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although the applied approach is practically equivalent to what can be found in the literature, the validity of the results is hard to confirm. Pappalardo managed to validate the home locations in the case of sixty-five subscribers [17], but this is not possible in this case. So, the settlement and -in the case of Budapest -district-based population data [2] is applied from the HCSO.…”
Section: Methodsmentioning
confidence: 99%
“…Pappalardo et al [17] compared the estimated home locations of sixty-five subscribers with the known geographical coordinates of their residence location, using different types of mobile network data: CDR, eXtended Detail Record (XDR) and Control Plane Record (CPR). It has been found that XDRs should be preferred when performing home location detection.…”
Section: Literature Reviewmentioning
confidence: 99%